Love Your Minds (mental health campaign awareness) / Nur Haziqah Abdul Khair - Abdul Khair, Nur Haziqah (2022)
Love Your Minds Is a mental health campaign and this campaign for UiTM Seri lskandar students. This is because students have a high percentage of depression, anxiety and stress. This campaign is to help overcome the problem of depression faced by students.